The Effect of Economic Growth, London Interbank Offered Rate (LIBOR), Exchange Rates and Covid-19 Pandemic on Foreign Direct Investment in Indonesia Period 2009-2023 - Hermaliza, Mingga; Widayatsari, Any; Kornita, Sri Endang (Universitas Muhammadiyah Prof. DR HAMKA., 2024)
This study examines the influence of Economic Growth, LIBOR, Exchange Rates, and the Covid-19 Pandemic on Foreign Direct Investment (FDI) in Indonesia from 2009 to 2023. A quantitative approach was used for analysis. The results reveal that, over the period studied, Economic Growth and LIBOR both have a positive but minimal impact on FDI in Indonesia. The Covid-19 Pandemic, represented as a dummy variable, shows a positive but statistically insignificant effect on FDI at a 5% significance level, though it has a significant impact at the 10% level. In contrast, Exchange Rates have a positive and significant effect on FDI.